Healthcare Professionals’ Compliance With Preventive Guidelines for Catheter-Associated Urinary Tract Infection at the Intensive Care Unit of a Tertiary Care Hospital - Tahira, Yasmin; Javaid, Asghar; Ashraf, Shazia; Nisa, Qamar-un- (Biological and Clinical Sciences Research Journal, 2025)
Catheter-associated urinary Tract Infection (CAUTI) is a substantial cause of morbidity, mortality and healthcare costs in ICUS. Adhering to the CDC’s CAUTI prevention recommendations is essential for reducing the risk of infection. The present study assessed HCPS’ perception and compliance with the CAUTI prevention guidelines and their relationship with rates of CAUTI in the ICU of Nishtar Hospital, Multan. Objectives: To evaluate the HCPS’ adherence to the CDC guidelines using the "observation checklist," to determine HCPS’ self-perception and the factors influencing compliance and examine the association between compliance and CAUTI rates during the six-month surveillance period. Methods: The current study used a descriptive cross-sectional design over six months in the ICU of Nishtar Hospital, Multan. Convenient sampling was used to select participants. Data were collected by a "checklist" through direct observation of HCPS’ adherence to CDC’s recommendations, and their perception of CDC guidelines and factors influencing adherence. The Chi-square test was used to analyze the association between adherence and CAUTI incidence. Results: 82% of respondents demonstrated good compliance, and 86% self-perception of the HCPS was good. 94% of HCPS reported that barriers were present which affected their compliance. The observed CAUTI rate was 60 per 1,000 catheter days, which exceeds the recommended threshold. A significant association was found between HCPS’ compliance and rates of CAUTI. Conclusion: These findings underscore the need to enhance adherence to the CDC’s CAUTI preventive guidelines for reducing CAUTI rates in the ICU setting. Implementing recommended protocols and overcoming obstacles leads to improved patient outcomes.